Upaya Mengembangkan Kreativitas Anak Usia 5-6 Tahun melalui Permainan Eksplorasi - Ade Tursina (Atfaluna: Journal of Islamic Early Childhood Education, 2018)
The problem in this research was: (1) low of creativity in 5-6-year-old children in TK Sandhy Putra Medan, (2) education system that focuses more on academic ability such as reading, writing and counting, (3) lack of facilities that can develop the creativity of children, (4) Children are less motivated by teachers in developing their creativity. This research aims to determine the creativity development of 5-6-year-old children by using the exploration game “sand play